MULTIPEL SKLEROSIS PROGRESIF SEKUNDER, GEJALA KLINIS, DIAGNOSIS, DAN TATA LAKSANA - Riwanti Estiasari; Nadia Devianca; Kartika Maharani; Darma Imran (NEURONA, 2020)
Multiple sclerosis (MS) is a chronic inflammatory autoimmune disorder of the central nervous system (CNS) affecting the myelin. MS is very detrimental which causes disability and will reduce the productivity and quality of life of the patients, especially if it progressed to secondary progressive multiple sclerosis (SPMS) which there will be a continuous worsening of neurological deficits. Early detection of symptom progression can be done to overcome the problems that may occur in SPMS. By early detection, immediate therapy of SPMS can be given thus preventing the progression. It is therefore important for us to know the definition of SPMS, how to detect progression, and the treatment options for SPMS that will be explained in this literature review. Keywords: Progression, therapy, SPMS